2016
DOI: 10.1016/j.neuropharm.2015.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of social deficits by subchronic oxytocin in two autism mouse models

Abstract: Social deficits are a hallmark feature of autism spectrum disorder (ASD) and related developmental syndromes. Although there is no standard treatment for social dysfunction, clinical studies have identified oxytocin as a potential therapeutic with prosocial efficacy. We have previously reported that peripheral oxytocin treatment can increase sociability and ameliorate repetitive stereotypy in adolescent mice from the C58/J model of ASD-like behavior. In the present study, we determined that prosocial oxytocin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 71 publications
2
43
0
Order By: Relevance
“…Oxt ( Ferguson et al, 2000 ; Ferguson et al, 2001 ) or Oxtr ( Sala et al, 2011 ; Pobbe et al, 2012a , b ) knockout (KO) mice have been reported to exhibit less social communication and interaction, along with impaired social cognitive memory and other altered behaviors relevant to ASD ( Zhang et al, 2017 ). Central infusion or peripheral injection of OXT has been shown to promote social approach ( Lukas et al, 2011 ; Teng et al, 2016 ), pair bonding ( Bales and Carter, 2003 ; Bales et al, 2007 ; Ross et al, 2009 ), and social memory ( Popik and van Ree, 1991 ; Benelli et al, 1995 ) in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Oxt ( Ferguson et al, 2000 ; Ferguson et al, 2001 ) or Oxtr ( Sala et al, 2011 ; Pobbe et al, 2012a , b ) knockout (KO) mice have been reported to exhibit less social communication and interaction, along with impaired social cognitive memory and other altered behaviors relevant to ASD ( Zhang et al, 2017 ). Central infusion or peripheral injection of OXT has been shown to promote social approach ( Lukas et al, 2011 ; Teng et al, 2016 ), pair bonding ( Bales and Carter, 2003 ; Bales et al, 2007 ; Ross et al, 2009 ), and social memory ( Popik and van Ree, 1991 ; Benelli et al, 1995 ) in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…These NR1 neoÀ/À mice may demonstrate behavioral phenotypes associated with ASD, including perturbed sociality (Barkus et al, 2012;Gandal et al, 2012a,b). Of note, this perturbed sociability may be selective to males (Barkus et al, 2012) and reversible with oxytocin administration (Teng et al, 2016). Deficits in sociability are absent when the NR1 neoÀ/À knockout is induced in adult mice (Belforte et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some inbred mouse strains expressing phenotypes relevant to autism are also used as autism models. Several studies revealed that C58/J mice displayed increased activity and repetitive behaviors, as well as less social approach in the three-chamber test [48][49][50][51] . Environmental enrichment (rearing in enriched cages) was reported to reduce repetitive behaviors and improve reversal learning in this strain [52,53] .…”
Section: Effect Of Environmental Enrichment On Inbred Mouse Models Ofmentioning
confidence: 99%